2019
DOI: 10.1111/1440-1681.13203
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐147b suppresses the proliferation and invasion of non‐small‐cell lung cancer cells through downregulation of Wnt/β‐catenin signalling via targeting of RPS15A

Abstract: | INTRODUC TI ONLung cancer, 85% of which is non-small-cell lung cancer (NSCLC), is the leading cause of cancer-related death in both males and females worldwide. 1 Most lung cancer patients are diagnosed at an advanced stage, and therefore have an extremely low 5-year survival rate. 2 Although great advances have been made in cancer therapeutic strategies over the past decade, the high recurrence rate still poses a high risk of decreased patient survival. 3 Therefore, elucidation of the elaborate molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…25 RPS15A was identified as a novel target for miR-147b in NSCLC (Nonsmall cell lung carcinoma) cells. 52 Likewise, in our study, we found that downregulation of RPS15A in PC3, NCI-H660 and NE-LNCaP cell lines highlighting a negative correlation between RPS15A and miR-147b expression in both in-vitro differentiated and NE cell lines of PCa.…”
Section: Conflict Of Interest Statementsupporting
confidence: 81%
See 1 more Smart Citation
“…25 RPS15A was identified as a novel target for miR-147b in NSCLC (Nonsmall cell lung carcinoma) cells. 52 Likewise, in our study, we found that downregulation of RPS15A in PC3, NCI-H660 and NE-LNCaP cell lines highlighting a negative correlation between RPS15A and miR-147b expression in both in-vitro differentiated and NE cell lines of PCa.…”
Section: Conflict Of Interest Statementsupporting
confidence: 81%
“…al, the systematic analysis of quantitative proteomics data obtained from IL‐6 induced NE differentiated LNCaP cells revealed that RPS15A is downregulated in NE LNCaP cells differentiated with IL‐6 in in vitro 25 . RPS15A was identified as a novel target for miR‐147b in NSCLC (Non‐small cell lung carcinoma) cells 52 . Likewise, in our study, we found that downregulation of RPS15A in PC3, NCI‐H660 and NE‐LNCaP cell lines highlighting a negative correlation between RPS15A and miR‐147b expression in both in‐vitro differentiated and NE cell lines of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the functions of RPS15A in various biological processes have been clari ed, such as being responsible for the regulation of cell division and participating in tumor progression [17,29]. In particular, the role of RPS15A in tumor progression has been increasingly recognized [15,19,22,[30][31][32][33]. Therefore, RPS15A is currently considered as a promising target for cancer therapy in the design of potent anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…ING5 overexpression promotes phosphorylation of β‐catenin at Ser33/37, leading to a decreased β‐catenin protein level [ 201 ]. The protein level of β‐catenin could also be manifested as active β‐catenin (unphosphorylated at Ser33/Ser37/Thr41), which is negatively regulated by miR-147b [ 202 ], and EXT1 [ 203 ].…”
Section: The Negative Regulators Of Wnt/β-catenin Signalingmentioning
confidence: 99%